THE MAIN DIRECTIONS OF THE ENERGY EFFICIENCY OF RAILWAY TRANSPORT OF UKRAINE - Malyshko, I. V. (Science and Transport Progress, 2006)
In the article there are the considered basic directions of energy economy on the railway transport ofUkraine.